Does the Method of Content Delivery Matter? Randomized Controlled Comparison of an Internet-Based Intervention for Eating Disorder Symptoms With and Without Interactive Functionality. Issue 3 (May 2022) - Linardon, Jake; Messer, Mariel; Shatte, Adrian; Greenwood, Christopher J.; Rosato, John; Rathgen, April; Skvarc, David; Fuller-Tyszkiewicz, Matthew
Highlights: Tested the benefit of interactive functionality in an Internet intervention. Interactive functionality included videos, quizzes, and a smartphone app. Dropout was significantly lower in the interactive than static group. Interactivity did not impact engagement and symptom reduction outcomes. Abstract: Despite their potential as a scalable, cost-effective intervention format, self-guided Internet-based interventions for eating disorder (ED) symptoms continue to be associated with suboptimal rates of adherence and retention. Improving this may depend on the design of an Internet intervention and its method of content delivery, with interactive programs expected to be more engaging than static, text-based programs. However, causal evidence for the added benefits of interactive functionality is lacking. We conducted a randomized controlled comparison of an Internet-based intervention for ED symptoms with and without interactive functionality. Participants were randomized to a 4-week interactive ( n = 148) or static ( n = 145) version of an Internet-based, cognitive-behavioral program. The interactive version included diverse multimedia content delivery channels (video tutorials, graphics, written text), a smartphone app allowing users to complete the required homework exercises digitally (quizzes, symptom tracking, self-assessments), and progress monitoring features. The static version delivered identical intervention content but only via written text, and contained none of those interactive features. Dropout rates were high overall (58%), but were significantly—yet slightly—lower for the interactive (51%) compared to the static intervention (65%). There were no significant differences in adherence rates and symptom-level improvements between the two conditions. Adding basic interactive functionality to a digital intervention may help with study retention. However, present findings challenge prior speculations that interactive features are crucial for enhancing user engagement and symptom improvement.